2014
DOI: 10.1021/sb500035y
|View full text |Cite
|
Sign up to set email alerts
|

Modularized CRISPR/dCas9 Effector Toolkit for Target-Specific Gene Regulation

Abstract: The ability to control mammalian genes in a synergistic mode using synthetic transcription factors is highly desirable in fields of tissue engineering, stem cell reprogramming and fundamental research. In this study, we developed a standardized toolkit utilizing an engineered CRISPR/Cas9 system that enables customizable gene regulation in mammalian cells. The RNA-guided dCas9 protein was implemented as a programmable transcriptional activator or repressor device, including targeting of endogenous loci. For fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 9 publications
1
15
0
Order By: Relevance
“…For example, rAAV-delivered Cas9 expression in vivo has the potential to last for years and even an entire lifetime in recipients. In addition, the catalytically dead Cas9 (dCas9) fused with effector protein domains has been shown to either activate or silence specific gene expression at the transcriptional level, representing a versatile approach to regulating gene expression[35][36][37] . This usually requires the continuing presence of dCas9-effector to exert a stable gene regulatory effect.…”
mentioning
confidence: 99%
“…For example, rAAV-delivered Cas9 expression in vivo has the potential to last for years and even an entire lifetime in recipients. In addition, the catalytically dead Cas9 (dCas9) fused with effector protein domains has been shown to either activate or silence specific gene expression at the transcriptional level, representing a versatile approach to regulating gene expression[35][36][37] . This usually requires the continuing presence of dCas9-effector to exert a stable gene regulatory effect.…”
mentioning
confidence: 99%
“…It took a while before this study was followed by ZF-targeting the HER2/neu gene in cancer [66] and even in vivo by targeting the murine  Fosb  gene [67•]. Similarly, authors have fused a TALE, targeting the E - Cadherin gene, and dCas9, in combination with sgRNAs to target VEGF - A , to the SET domain of the histone methyltransferase G9a and demonstrated that this approach is effective in repressing genes, as seen with ZFPs [68, 69]. In the meantime, Zinc Fingers were also exploited in the first DNA methylation targeting studies by fusion to the catalytic domains of DNA methyltransferases Dnmt3a or including a fusion between Dnmt3a and Dnmt3L, which catalyze the de novo methylation of DNA.…”
Section: Epigenetic Repressionmentioning
confidence: 99%
“…The procedure is easy and fast (a single cloning step, virus production, and transduction), worked with 70% to 100% efficiency (depending on the assay-T7 endonuclease assay or sequencing), and was specific for the target site. To this end, the endonuclease activity of Cas9 is disabled through the insertion of point mutations, and the mutant Cas9 is fused to transcriptional activator or repressor domains (e.g., Agne et al, 2014). Here, simultaneous single-strand breaks (nicks) at opposite strands of the DNA target site using a mutant version of Cas9 and appropriately spaced guide RNAs create double-stranded breaks while increasing the specificity for cleavage.…”
Section: Of the Human Fbxl3 Locus Consists Of A 20-nt Guide Sequence mentioning
confidence: 99%